Earthworms Building Up Soil Microbiota, a Review - Medina-Sauza, Regina M.; Álvarez-Jiménez, Marycruz; Delhal, Alix; Reverchon, Frédérique; Blouin, Manuel; Guerrero-Analco, José A.; Cerdán, Carlos R.; Guevara, Roger; Villain, Luc; Barois, Isabelle (Frontiers in Environmental Science, 2019)
The positive effect of earthworms on soil processes and plant growth has been extensively documented. The capacity of earthworms to decompose organic matter has been attributed to the microbial communities that inhabit their digestive track or the structures they build, which in turn contribute to make up the drilosphere, a hotspot for microbial activity. However, how earthworms modify the structure of soil microbial communities and how these changes affect soil microbial processes is still unclear. Do earthworms reduce microbial abundance and activity because they feed on microorganisms or do they select and stimulate specific microbial groups? We hypothesise that “the effect of earthworms on nutrient cycling and plant growth is not only a direct effect but is mainly mediated indirectly, via modifications of the microbial community.” The objective of this review is to synthesize the existing literature concerning the influence of earthworms on the structure and function of soil microbial communities, as well as to understand how earthworm-induced changes in the soil microbiota would in turn impact soil processes, particularly those occurring in the rhizosphere and involved in plant growth and health. Recent reports have shown that specific bacterial groups consistently increase in soils where earthworms are present, regardless of the earthworm functional group. The extent of this increase seems to be dependent upon the type of substrate under study. Our synthesis also reveals that endogeic and anecic earthworms regularly induce an increase in soil nutrients, whilst this positive effect is not as evident in the presence of epigeic earthworms. The effect of earthworms on nutrient cycling has been further investigated with microbial functional genes, although existing reports largely focus on nitrogen cycling. Earthworms seem to enhance denitrification, most likely through the increase in organic compounds due to organic matter decomposition. By enhancing soil nutrient availability, earthworms indirectly promote plant growth, which has also been attributed to the induction of signal molecules. However, no experiment to date has been able to prove a direct causal relationship between specific signal molecules, earthworms and plant growth promotion. Finally, we propose a framework for earthworm-microbiota interactions and recommend further research.